Pendekatan Kreatif dalam Edukasi Lingkungan Melalui Pelatihan Daur Ulang Stik Es Krim di Gampong Cot Gud, Aceh Besar - Mery Silviana; Lindawati Lindawati; Amalia Amalia; Mislinawati Mislinawati; Wiwin Apriani (Jurnal Pengabdian Masyarakat: Darma Bakti Teuku Umar, 2026)
One type of waste that is often overlooked is small wood waste, such as ice cream sticks. Ice cream stick wood has great potential to be repurposed into products that are both functional and economically valuable. This community service activity aims to educate children in Cot Gud Village on how to transform ice cream stick waste into functional and educational handicrafts. The training was conducted through a combination of socialization, demonstrations, and hands-on practice in a fun and interactive manner under the supervision of facilitators. The results of the activity show that this creative approach successfully increased children's environmental awareness, technical skills, and active participation. The handcrafted products made by the children of Cot Gud Village were also of good quality. In addition to reducing waste, this activity also served as a means of character education, collaboration, and critical thinking development for the children. It can be concluded that such activities are effective as a strategy for environmental education and community-based empowerment.